Angelica Dahurica Regulated the Polarization of Macrophages and Accelerated Wound Healing in Diabetes: A Network Pharmacology Study and In Vivo Experimental Validation - Hu, Yonghui; Lei, Sisi; Yan, Zhiyue; Hu, Zhibo; Guo, Jun; Guo, Hang; Sun, Bei; Pan, Congqing (Frontiers in Pharmacology, 2021)
Diabetic wounds exhibit retarded and partial healing processes. Therefore, patients are exposed to an elevated risk of infection. It has been verified that Angelica dahurica (Hoffm.) Benth. & Hook.f. ex Franch. & Sav (A. dahurica) is conducive for wound healing. However, the pharmacological mechanisms of A. dahurica are yet to be established. The present study uses network pharmacology and in vivo experimental validation to investigate the underlying process that makes A. dahurica conducive for faster wound healing in diabetes patients. 54 potential targets in A. dahurica that act on wound healing were identified through network pharmacology assays, such as signal transducer and activator of transcription 3 (STAT3), JUN, interleukin-1β (IL-1β), tumor necrosis factor (TNF), and prostaglandin G/H synthase 2 (PTGS2). Furthermore, in vivo validation showed that A. dahurica accelerated wound healing through anti-inflammatory effects. More specifically, it regulates the polarization of M1 and M2 subtypes of macrophages. A. dahurica exerted a curative effect on diabetic wound healing by regulating the inflammation. Hence, pharmacologic network analysis combined with in vivo validation elucidated the probable effects and underlying mechanisms of A. dahurica’s therapeutic effect on diabetic wound healing.